2021
DOI: 10.1017/s0007114521003809
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition as a risk factor of adverse postoperative outcomes in patients undergoing hepatic resection: analysis of US hospitals

Abstract: In patients with liver cancer or space-occupying cysts, they suffer from malnutrition due to compression of gastric and digestive structures, liver and cancer-mediated dysmetabolism, and impaired nutrient absorption. As proportion of these patients require removal of lesions through hepatic resection, it is important to evaluate the effects of malnutrition on post-hepatectomy outcomes. In our study approach, 2011-2017 National Inpatient Sample was used to isolate in-hospital hepatectomy cases, which were strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Impaired nutrition affects many immune system domains, including the complement system, opsonization, and leukocyte function, leading to increased postoperative nosocomial infections. 1 Previous studies have identified obesity as associated with higher postoperative complications; however, BMI alone cannot identify malnutrition or nutritional risk. [12][13][14] Our results specifically reveal that among those who lose significant weight before surgery, those at the highest risk are underweight, average weight, or morbidly obese.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Impaired nutrition affects many immune system domains, including the complement system, opsonization, and leukocyte function, leading to increased postoperative nosocomial infections. 1 Previous studies have identified obesity as associated with higher postoperative complications; however, BMI alone cannot identify malnutrition or nutritional risk. [12][13][14] Our results specifically reveal that among those who lose significant weight before surgery, those at the highest risk are underweight, average weight, or morbidly obese.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired nutrition affects many immune system domains, including the complement system, opsonization, and leukocyte function, leading to increased postoperative nosocomial infections. 1…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 2,531 patients undergoing hepatectomy, Lee et al. ( 21 ) reportedly had a higher occurrence of bleeding, infection, wound complication, and respiratory failure in the malnutrition cohort. A similar finding was also confirmed in other solid malignancies ( 22 ), but there are only a few reports regarding head and neck cancers.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19] Malnutrition also increases postoperative mortality in liver surgery. 20 Similar to poor nutritional status, frailty affects outcomes negatively in short and long term after colorectal cancer surgery and liver resection. Assessment of frailty is complex and includes baseline functional status, cognitive function, physical health, comorbidities, social status, and nutritional status.…”
Section: Patient Selection Nutritional Status and Frailtymentioning
confidence: 99%